2004
DOI: 10.1161/01.res.0000108262.35847.60
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A 3 Receptor Activation Modulates the Capillary Endothelial Glycocalyx

Abstract: Abstract-The endothelial glycocalyx is a dynamic extracellular matrix composed of cell surface proteoglycans, glycoproteins, and adsorbed serum proteins that has been implicated in the regulation and modulation of capillary tube hematocrit, permeability, and hemostasis. High tissue adenosine levels have been shown to adversely affect microvascular function and tissue survival after an ischemic episode, and previous work in this laboratory has shown that adenosine causes arteriolar constriction and degranulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
88
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 36 publications
9
88
0
2
Order By: Relevance
“…The effect of adenosine on the glycocalyx does not necessarily have to reflect a true physical degradation of this layer. Rather, an increase in glycocalyx porosity might be involved because the decrease in exclusion of dextrans was found to be much more profound, and to occur at lower concentrations, than that of red blood cells (21). In a previous study of the Duling group, systemic administration of hyaluronidase was equally found to increase glycocalyx porosity independently from a change in the physical dimensions of the layer as judged from the exclusion of red blood cells (6).…”
Section: Rh Vs Ahmentioning
confidence: 93%
See 4 more Smart Citations
“…The effect of adenosine on the glycocalyx does not necessarily have to reflect a true physical degradation of this layer. Rather, an increase in glycocalyx porosity might be involved because the decrease in exclusion of dextrans was found to be much more profound, and to occur at lower concentrations, than that of red blood cells (21). In a previous study of the Duling group, systemic administration of hyaluronidase was equally found to increase glycocalyx porosity independently from a change in the physical dimensions of the layer as judged from the exclusion of red blood cells (6).…”
Section: Rh Vs Ahmentioning
confidence: 93%
“…These results might be explained by an increased accessibility of the glycocalyx by circulating blood as suggested by intravital microscopic observations of an impaired ability of the glycocalyx to exclude 70-kDa FITC-dextrans and red blood cells during adenosine superfusion in cremaster capillaries (21). The effect of adenosine on the glycocalyx does not necessarily have to reflect a true physical degradation of this layer.…”
Section: Rh Vs Ahmentioning
confidence: 93%
See 3 more Smart Citations